ENTRE A CULPA E O PECADO: UMA ABORDAGEM LITERÁRIO-TEOLÓGICA NO POEMA “A JESUS CRISTO NOSSO SENHOR” DE GREGÓRIO DE MATOS - RIPOLI, SHEILA ALVES (2020)
This research will address the issues applied to Brazilian Baroque literary analysis in the present poem attributed to the poet Gregório de Matos and will give attention to the discourse agents who will read the poem textualizing it. As a result of the research, we will look at the literary-theological method with a bias of the theopoetic approach looking at the conflicting situations of the government and the clergy regarding the hardship of the time under study. Next, we present the chronology of Gregório de Matos’ life, including the moments in which the poet appeared in the Brazilian Baroque period. We will also point out which interactions will facilitate the analysis of the poem A Jesus Christ Our Lord based on the studies of the said sin and guilt and if it is possible to find, behind these words, human freedom or free will.